Evaluation of Turkey-Iraq relations in terms of hydropolitics (Eurasian Journal of Engineering and Technology, 2022)
World temperature averages are constantly increasing in parallel with global warming. As a natural result of this, World water resources are decreasing rapidly. Unless this situation changes, water will appear as a decreasing value. Water is a very serious problem due to high temperatures, especially for some generations closer to the equatorial area. The richest country in water when the overall evaluation of the region is Turkey. Neighboring countries are dependent on Turkey, Syria and Iraq is a case in water. The problem stems from this situation. Turkey wants to exercise the rights conferred on it by international treaties on the sharing of water. The vast majority of Turkey owned water resources in the region stems from the mountains in eastern Anatolia. Therefore, Turkey is willing to have power over these waters. However, it also pays attention to the issue of equity by allowing the flow of water to its neighbors. With the dams it has built in the region, it has aimed at the regular flow of water and the storage of water for periods when it is insufficient. The GAP project plays an active role in sharing water in the region. In this country, both bordered by Turkey, both under the project to sell water to other Middle Eastern countries. However, this causes projects not to be developed.